Pengaruh Kombinasi Anestesi Ketamine-Medetomidine dengan Premedikasi Acepromazine dan Atropine Sulfate terhadap Profil Hematologi Anjing Lokal - Tri Utami; Tarsisius Considus Tophianong; Yohanes T.R.M.R Simarmata; Yeremia Yobelanno Sitompul; Yustinus O.P Wuhan; Jayusman Arsiyanti (JURNAL KAJIAN VETERINER, 2026)
This study aimed to evaluate the effect of the combination of ketamine-medetomidine anesthesia with two different types of premedication, namely acepromazine and atropine sulfate, on hematological parameters in local dogs. A total of six male local dogs aged 1–2 years with a body weight of 8–15 kg were used as experimental animals and randomly divided into two groups (three dogs each). Group 1 was given acepromazine premedication (0.05 mg/kg BW, im), while group 2 was given atropine sulfate premedication (0.04 mg/kg BW, sc). Fifteen minutes later, both groups were induced with ketamine (10 mg/kg BW, im) and medetomidine (30 µg/kg BW, im). Blood samples were taken through the saphenous vein at three observation times: before anesthesia (T0), 30 minutes (T30), and 60 minutes (T60) after anesthesia. Parameters measured included total erythrocytes, hemoglobin levels, hematocrit values, and total leukocytes using a hematology analyzer. Data analysis showed no significant differences (p>0.05) between time points or between treatment groups. The erythrocyte, hemoglobin, hematocrit, and leukocyte counts in both groups remained within the normal physiological range. However, the group 1 showed a tendency for decreased hematological values after anesthesia due to the sedative effect of acepromazine, while the group 2 showed a transient increase due to the pre-anesthetic stress response and mild dehydration. The results of this study indicate that the combination of ketamine-medetomidine anesthesia with acepromazine or atropine sulfate premedication does not cause significant hematological changes and is safe for use in local dogs during clinical anesthetic procedures.